2017
DOI: 10.2217/fon-2017-0168
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Differentially Expressed Genes in Thyroid Cancer

Abstract: These results provide some novel findings on DEGs in thyroid cancer, which will be useful to guide further investigation and target therapy for this disease. [Formula: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…23 Target drugs on specific genes related to thyroid carcinoma, including BRAF and RET, contribute to improve the clinical outcome of affected people. 24 After active treatment of surgical resection combined radioactive iodine and thyroid hormone suppression therapy, thyroid carcinoma patients usually achieve a satisfied prognosis. 25 Previous studies have shown that RNA methylation accounts for over 60% of all RNA modifications, including m 6 A, m 1 A and m 5 C, etc.…”
Section: Discussionmentioning
confidence: 99%
“…23 Target drugs on specific genes related to thyroid carcinoma, including BRAF and RET, contribute to improve the clinical outcome of affected people. 24 After active treatment of surgical resection combined radioactive iodine and thyroid hormone suppression therapy, thyroid carcinoma patients usually achieve a satisfied prognosis. 25 Previous studies have shown that RNA methylation accounts for over 60% of all RNA modifications, including m 6 A, m 1 A and m 5 C, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Increased proliferation and cyclin activity are also hallmarks of cancer cells (Chai et al, 2016a), thus we aimed to characterize the expression of genes that have previously been shown to be up-or downregulated in thyroid cancer (Agrawal et al, 2014;Chai et al, 2016b;Costa et al, 2015;Wang et al, 2017). Interestingly, 72% of genes described as upregulated in thyroid cancer were downregulated in early passage (passage 0-2) organoids compared with primary tissue-derived cells, while some of these genes displayed further downregulation in later passage (passage 3-4) organoids ( Figure 4A, Table S3).…”
Section: Lack Of Thyroid Tumor Markers In Thyroid Organoidsmentioning
confidence: 99%
“…An investigation of differentially expressed genes (DEGs) between tumour and normal tissues may also help identify significant biomarkers. J. Wang et al () used the gene expression of 57 paired thyroid cancer and noncancerous tissues from the The Cancer Genome Atlas (TCGA) database to find 1,061 DEGs, including 752 upregulated and 309 downregulated genes. In addition, based on four Gene Expression Omnibus (GEO) microarray datasets, 225 commonly changed DEGs (111 upregulated and 114 downregulated) were identified (Liang & Sun, ).…”
Section: Introductionmentioning
confidence: 99%